Selenium and hepatocellular carcinoma - Nasar Alwahaibi,; Jamaludin Mohamed, (Penerbit UKM, 2008)
While cancer is considered to be one of the leading causes of death worldwide, there is a growing scientific and public interests on selenium as a dietary and antioxidant of many diseases, in particular, cancer. Despite advanced technology and significant improvement of surgical, chemical, hormonal and radio therapies, hepatocellular carcinoma (HCC) is still common in Asia and Africa and is increasing in the developed countries. Prognosis of HCC at an early stage is still challenging. At the moment, combination of Alpha feto protein (AFP) and ultrasonography tests offers more accurate and sensitive results for the diagnosis of HCC. Selenium (also known as the moon element) has been recognized for almost 49 years as an antioxidant and anti cancer agent. The weight of evidence supports the position of selenium as an anti cancer agent for HCC but the molecular mechanism of how selenium inhibits HCC is still unknown. Numerous theories have been proposed and selenium induced apoptosis and cell cycle arrest is the predominant one so far.